Collagen Induces Normal Signal Transduction in Platelets Deficient in CD36 (Platelet Glycoprotein IV) - Daniel, James L; Dangelmaier, Carol; Strouse, Robert; Smith, J Bryan (Thrombosis and Haemostasis, 1994)
The receptor involved in platelet activation by collagen has not been identified. Platelet glycoprotein IV, now known as CD36, has been implicated in interaction with collagen and also been shown to be associated with intracellular tyrosine kinases. In order to investigate the possible role of collagen-mediated signal transduction via CD36, platelets were obtained from a donor that were deficient in CD36. The collagen-induced intracellular mobilization of Ca2+ in the CD36 deficient cells was of the same magnitude as that seen in platelets from normal donors. In addition, serotonin secretion did not appear to be impaired. Tyrosine phosphorylation was also comparable between the CD36-deficient and normal platelets. Thus, it is unlikely that CD36 plays a major role in collagen-dependent platelet signal transduction.